SOUTH AMERICA AND EAST ASIA: DEPENDENCY AND DIVERSIFICATION DILEMMAS WITHIN AN ASYMMETRIC POWER STRUCTURE (2002-2017) - Rubiolo, M Florencia (PEOPLE: International Journal of Social Sciences, 2018)
Dependency on the power structure and on the most powerful actors within it, has been a constant variable in foreign policy calculation for the developing world. South American countries have shown in the last two decades an increasing will to overcome dependency on few traditional powers through diversification. It has led to a growing rapprochement to East Asia, mainly underpinned by the trade relation with China. Although the level of dependency is not the same in every country, there are some common features that show that bilateral relations are not interdependent: 1) it reinforces the concentration on low value-added products for South America, reproducing an extractivist export based model, undermining industrialization processes and 2) it reflects the profound power asymmetries between the two sides undermining, in the long run, state autonomy. In this paper, we aim to analyze the bilateral relations of the main South American economies –Argentina, Brazil and Chile- with China and their major ASEAN partners between 2002-2017. Our theoretical perspective is built upon the concepts of diversification, autonomy and dependency. Our goal is to understand the emergence of the dependent relationship with Beijing and the consequences it might bring to South America in terms of economic policy and development. On the other hand, we aim to explore the alternative scenario SEA countries constitute for a broader, less dependent and more symmetrical economic and political relation with East Asia.